Recent Changes in Glacier Facies Zonation on Devon Ice Cap, Nunavut, Detected from SAR Imagery and Field Validation Methods - de Jong, Johannes Tyler (Université d'Ottawa / University of Ottawa, 2013)
Glacier facies represent distinct regions of a glacier surface characterized by near surface structure and density that develop as a function of spatial variations in surface melt and accumulation. In post freeze-up (autumn) synthetic aperture radar (SAR) satellite imagery, the glacier ice zone and dry snow zone have a relatively low backscatter due to the greater penetration of the radar signal into the surface. Conversely, the saturation and percolation zones are identifiable based on their high backscatter due to the presence of ice lenses and pipes acting as efficient scatterers. In this study, EnviSat ASAR imagery is used to monitor the progression of facies zones across Devon Ice Cap (DIC) from 2004 to 2011. This data is validated against in situ surface temperatures, mass balance data, and ground penetrating radar surveys from the northwest sector of DIC. Based on calibrated (sigma nought) EnviSat ASAR backscatter values, imagery from autumn 2004 to 2011 shows the disappearance of the ‘pseudo’ dry snow zone at high elevations, the migration of the glacier and superimposed ice zones to higher elevations, and reduction in area of the saturation/percolation zone. In 2011, the glacier and superimposed ice zone were at their largest extent, occupying 92% of the ice cap, leaving the saturation/percolation zone at 8% of the total area. This is indicative of anomalously high summer melt and strongly negative mass balance conditions on DIC, which results in the infilling of pore space in the exposed firn and consequent densification of the ice cap at higher elevations.
Keywords: Glacier; Glacier facies; Glaciology; Devon Ice Cap; Devon Island